Microbial Quality and Antibacterial Activity of Herbal Medicines - Shah, Bibha; Pokhrel, Nabaraj (Nepal Journal of Science and Technology, 2013)
Use of herbal medicine faces constraint particularly imparting knowledge in identifying whether a product is microbiologically fit for health or not. There has been relatively less research on microbial quality of the herbal medicines in Nepal. In this context, this research has focused on microbial quality of different herbal medicines. A total of twenty one herbal medicines were collected from different sales outlet of Kathmandu. The microbial load in herbal medicine was determined by aerobic plate count method and bacterial isolates were identified based on morphological, cultural and biochemical tests. Out of twenty one herbal medicines analyzed, all were found free from pathogenic bacteria and indicator organism of fecal contamination. However , Bacillus spp. were isolated from ten herbal medicines. The microbial load on Nutrient Agar was found within the range of 1.20x103- 6.06x105 cfu/ ml (or g). Altogether six different Bacillus spp were identified and the most predominant was Bacillus subtilis. In vitro antibacterial activity of the herbal medicines, from which microorganisms were not detected, were determined against six test bacteria by cup plate method. Out of eleven different herbal medicines, five showed the zone of inhibition against all test bacteria and at least two test bacteria were inhibited by each of the herbal medicines. The highest zone of inhibition was 30 mm shown by Chitrakaharitaki Churna of concentration 100mg/ml against Pseudomonas aeruginosa. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 191-196 DOI: http://dx.doi.org/10.3126/njst.v13i2.7735